2016
DOI: 10.1080/19768354.2016.1266287
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the alula in relation to wing and body size in the Laridae and Sternidae

Abstract: The alula is a small structure present on the leading edge of bird wings and is known to enhance lift by creating a small vortex at its tip. Alula size vary among birds, but how this variation is associated with the function of the alula remains unclear. In this study, we investigated the relationship between the size and shape of the alula and the features of the wing in the Laridae and Sternidae. Laridae birds have generally longer wings and greater loadings than Sternidae birds. The two families differed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Scaling trends in flight feathering. Measurements of the alular feathers are sparse in the literature 7,10,11 .…”
mentioning
confidence: 99%
“…Scaling trends in flight feathering. Measurements of the alular feathers are sparse in the literature 7,10,11 .…”
mentioning
confidence: 99%
“…Each final wing shape was attached to a gull-inspired body. We selected a NACA0020 aerofoil based on an estimated body length (41 cm) and body height that was estimated using an allometric relationship with a body mass of 0.91 kg [34,35]. The shoulder joint was positioned at the quarter-chord of the body.…”
Section: Determining the Wing-body Configurationsmentioning
confidence: 99%
“…Through a summary and analysis of the current research, we can find that some pretty good insights have been gained from studies on the alula. Firstly, studies have found that the alula is mostly used by birds during takeoff and landing, playing the role of delaying flow separation and increasing lift, similar to high-lift devices in fixed-wing aircraft [1,2]. Secondly, there have been two main predictions regarding the aerodynamic mechanisms underlying the lift enhancement of the alula, which are the leading-edge slot effect [4,5] and the vortex generator effect [6].…”
Section: Aerodynamic Mechanism Of the Alulamentioning
confidence: 99%
“…Also their results showed that the ratio of the length of the alula to the wing span decreases with the increasing aspect ratio of the wing. Lee and Choi [2] investigated the relationship between the size and shape of the alula and the features of the wing in the Laridae and Sternidae. They found that for Laridae, the aspect ratio of the alula was smaller in the species that have relatively longer wings, but the pattern was opposite in the Sternidae, the species with high loading potential and long wings exhibit long alula.…”
Section: Morphological Measurements and Statistics Of The Alulamentioning
confidence: 99%
See 1 more Smart Citation